2023
DOI: 10.1371/journal.pone.0281854
|View full text |Cite
|
Sign up to set email alerts
|

Passion fruit plants alter the soil microbial community with continuous cropping and improve plant disease resistance by recruiting beneficial microorganisms

Abstract: Passion fruit (Passiflora edulis) is widely grown in tropical and subtropical regions, showing high economic and ornamental value. Microorganisms are indicators for the stability and health of the soil ecosystem, which can affect the yield and quality of passion fruit under continuous cropping. High-throughput sequencing and interactive analysis were used to analyse the variation of microbial communities in the noncultivated soil (NCS), cultivated soil (CS), and the rhizosphere soil of purple passion fruit (Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Our data show that the wild-type had a decrease in mean fresh weight due to the effects of continuous cropping, which have been shown to lead to crop growth retardation or yield reduction, , whereas rps2 plants showed significantly better growth in the third generation after successive Pst infections. The reason for this phenomenon may be that under the invasion of the same pathogen, the A. thaliana selectively enrich beneficial microorganisms at the rhizosphere, improving its immunity and passing on its legacy to the next generation. , It has been shown that continuous planting of crops (tomato, wheat, and common bean), for example, can maintain plant health despite exposure to pathogens. Wang et al found that continuous cultivation of passion fruit increased plant disease resistance by altering the soil microbial community and by recruiting beneficial microorganisms. The exudation pattern of the plants was altered to recruit relevant beneficial microorganisms to the rhizosphere and trigger the spread of the soil legacy, maximizing the resistance of the next plant generation …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data show that the wild-type had a decrease in mean fresh weight due to the effects of continuous cropping, which have been shown to lead to crop growth retardation or yield reduction, , whereas rps2 plants showed significantly better growth in the third generation after successive Pst infections. The reason for this phenomenon may be that under the invasion of the same pathogen, the A. thaliana selectively enrich beneficial microorganisms at the rhizosphere, improving its immunity and passing on its legacy to the next generation. , It has been shown that continuous planting of crops (tomato, wheat, and common bean), for example, can maintain plant health despite exposure to pathogens. Wang et al found that continuous cultivation of passion fruit increased plant disease resistance by altering the soil microbial community and by recruiting beneficial microorganisms. The exudation pattern of the plants was altered to recruit relevant beneficial microorganisms to the rhizosphere and trigger the spread of the soil legacy, maximizing the resistance of the next plant generation …”
Section: Discussionmentioning
confidence: 99%
“…40,41 It has been shown that continuous planting of crops (tomato, wheat, and common bean), for example, can maintain plant health despite exposure to pathogens. 42−44 Wang et al 45 found that continuous cultivation of passion fruit increased plant disease resistance by altering the soil microbial community and by recruiting beneficial microorganisms. The exudation pattern of the plants was altered to recruit relevant beneficial microorganisms to the rhizosphere and trigger the spread of the soil legacy, maximizing the resistance of the next plant generation.…”
Section: Discussionmentioning
confidence: 99%
“…To promote soil suppressiveness, beneficial microbes in the rhizosphere can be enriched by promoting their assembly ( Chen et al., 2020a ; Leite et al., 2023 ; Wang et al., 2023c ; Wantulla et al., 2023 ) or transferring pathogen-suppressive microbes into conducive soils ( Zhao et al., 2021b ; Shao et al., 2022 ; Sritongon et al., 2023 ). These enrichments have shown a great potential for improving plant health through minimized disease pressure.…”
Section: Soil Suppressiveness To Phytopathogens In the Rhizospherementioning
confidence: 99%
“…Scientists argue whether changes in the microbiome structures are causal factors leading to diseases ( Li et al., 2023a ) or if they are merely consequences of diseases ( Kuang et al., 2023 ). Yet more investigations are needed to determine this phenomenon, numerous studies have demonstrated that the enhanced pathogen suppression in the rhizosphere is the result of changes in microbiome composition ( Carrión et al., 2019 ; Chen et al., 2020a ; Chen et al., 2022 ; Hong et al., 2023 ; Khatri et al., 2023b ; Wang et al., 2023c ; Zhu et al., 2023 ). Nevertheless, limited efforts have been devoted to systematic manipulation of the rhizosphere microbiome however, more insights have been gained through simplification of the core microbiome and developing synthetic microbial communities ( Hong et al., 2023 ; Zheng et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to continuous large-scale planting over many years, rot-inducing pathogens in passion fruit stems, such as Fusarium oxysporum f. sp. Passiflorae and F. solani, have accumulated in the soil (Salazar et al, 2016;Wang et al, 2023b). This issue is often managed by pesticide disinfection, crop rotation or interplanting, soil improvements, and the breeding of resistant varieties.…”
Section: Introductionmentioning
confidence: 99%